Therapeutic strategies to overcome ALK-fusion and BRAF-mutation as acquired resistance mechanism in EGFR-mutated non-small cell lung cancer: two case reports - Zeng, Yuan; Zeng, Qiang; Yang, Bin (Frontiers in Oncology, 2024)
Non-small cell lung cancer (NSCLC) is one of the most common malignancies in the world. EGFR tyrosine inhibitors are the preferred first-line treatment for patients with epidermal growth factor-cell receptor mutant (EGFR mutant) advanced NSCLC. Unfortunately, drug resistance inevitably occurs leading to disease progression. Activation of the ALK and BRAF bypass signaling pathways is a rare cause of acquired drug resistance for EGFR-TKIs.We report two NSCLC-patients with EGFR- mutations, in exon 19, and exon 18, correspondingly, who were treated with EGFR-TKIs. The first case shows acquired BRAF-mutation, and the second case demonstrates acquired ALK-fusion. The overall survival of patients was significantly prolonged by drug-match therapies. As it is well-known that ALK-fusion and BRAF-mutations are described forms of acquired resistance. These two case reports contribute to the previous reports that ALK-fusion and BRAF-mutation are potential underlying mechanisms of EGFR-TKI resistance.